Population Density and Risk of Inflammatory Bowel Disease: A Prospective Population-Based Study in 13 Countries or Regions in Asia-Pacific. (January 2019) - Ng, Siew C.; Kaplan, Gilaad G.; Tang, Whitney; Banerjee, Rupa; Adigopula, Bhargavi; Underwood, Fox E.; Tanyingoh, Divine; Wei, Shu-Chen; Lin, Wei-Chen; Lin, Hung-Hsin; Li, Jin; Bell, Sally; et al.
Abstract : INTRODUCTION: Living in an urban environment may increase the risk of developing inflammatory bowel disease (IBD). It is unclear if this observation is seen globally. We conducted a population-based study to assess the relationship between urbanization and incidence of IBD in the Asia-Pacific region. METHODS: Newly diagnosed IBD cases between 2011 and 2013 from 13 countries or regions in Asia-Pacific were included. Incidence was calculated with 95% confidence interval (CI) and pooled using random-effects model. Meta-regression analysis was used to assess incidence rates and their association with population density, latitude, and longitude. RESULTS: We identified 1175 ulcerative colitis (UC), 656 Crohn's disease (CD), and 37 IBD undetermined (IBD-U). Mean annual IBD incidence per 100 000 was 1.50 (95% CI: 1.43–1.57). India (9.31; 95% CI: 8.38–10.31) and China (3.64; 95% CI, 2.97–4.42) had the highest IBD incidence in Asia. Incidence of overall IBD (incidence rate ratio [IRR]: 2.19; 95% CI: 1.01–4.76]) and CD (IRR: 3.28; 95% CI: 1.83–9.12) was higher across 19 areas of Asia with a higher population density. In China, incidence of IBD (IRR: 2.37; 95% CI: 1.10–5.16) and UC (IRR: 2.63; 95% CI: 1.2–5.8) was positively associated with gross domestic product. A south-to-north disease gradient (IRR: 0.94; 95% CI: 0.91–0.98) was observed for IBD incidence and a west-to-east gradient (IRR: 1.14; 95% CI: 1.05–1.24) was observed for CD incidence in China. This study received IRB approval. CONCLUSIONS: Regions in Asia with a high population density had a higher CD and UC incidence. Coastal areas within China had higher IBD incidence. With increasing urbanization and a shift from rural areas to cities, disease incidence may continue to climb in Asia.